1993
DOI: 10.1121/1.406882
|View full text |Cite
|
Sign up to set email alerts
|

Internal stress wave measurements in solids subjected to lithotripter pulses

Abstract: Semiconductor strain gauges were used to measure the internal strain along the axes of spherical and disk plaster specimens when subjected to lithotripter shock pulses. The pulses were produced by one of two lithotripters. The first source generates spherically diverging shock waves of peak pressure approximately 1 MPa at the surface of the specimen. For this source, the incident and first reflected pressure (P) waves in both sphere and disk specimens were identified. In addition, waves reflected by the disk c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…One important mechanism is cavitation (Coleman et al 1987;Crum 1988). Other mechanisms such as spallation (Chaussy et al 1980), shear stress (Gracewski et al 1993) and squeezing (Eisenmenger 2001(Eisenmenger , 2002 are also important. A number of studies suggest the importance of cavitation collapse in SWL ( Bailey 1997;Carnel et al 1993;Cathignol et al 1998;Church 1989;Philip et al 1993;Pishchalnikov et al 2003;Sapozhnikov et al 2002) and the control of the cavitation has been attempted.…”
Section: Introductionmentioning
confidence: 98%
“…One important mechanism is cavitation (Coleman et al 1987;Crum 1988). Other mechanisms such as spallation (Chaussy et al 1980), shear stress (Gracewski et al 1993) and squeezing (Eisenmenger 2001(Eisenmenger , 2002 are also important. A number of studies suggest the importance of cavitation collapse in SWL ( Bailey 1997;Carnel et al 1993;Cathignol et al 1998;Church 1989;Philip et al 1993;Pishchalnikov et al 2003;Sapozhnikov et al 2002) and the control of the cavitation has been attempted.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, numerous studies have been conducted to dissect the role of stress waves and cavitation in stone fracture (Zhu et al, 2002;Sapozhnikov et al, 2007). Many proposed mechanisms, such as spallation (Lubock, 1989), geometric superfocusing (Gracewski et al, 1993;Xi and Zhong, 2001), circumferential squeezing (Eisenmenger, 2001), and shear-induced failure (Xi and Zhong, 2001;Cleveland and Sapozhnikov, 2005;Sapozhnikov et al, 2007) were demonstrated during the fragmentation process in the early stage of SWL, when the stones are of sufficient size to favor the development of large stress concentrations. Other proposed mechanisms, such as dynamic fatigue (Lokhandwalla and Sturtevant, 2000) and cavitation (Coleman et al, 1987;Sass et al, 1991;Philipp and Lauterborn, 1998), describe processes that influence stone fragmentation throughout the entire course of SWL.…”
Section: Introductionmentioning
confidence: 99%
“…SWL has been clinically used to treat kidney stones since 1980, 1,2 but there is still debate over the process by which the SWs comminute kidney stones. There are two main categories of mechanisms deemed plausible for stone breakage: direct stress effects, such as spallation, 1,3 squeezing, 4 shear, 5,6 and cavitation effects consisting of microjets, 7,8 and secondary SWs emitted from collapsing bubbles. [9][10][11][12] Studies have shown that altering the temporal wave profile can affect cavitation, [13][14][15][16][17][18][19] thus influencing the cavitation related mechanisms of therapeutic ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Similarly, mechanisms such as squeezing and shear depend more on the pressure at the periphery of the stone. [4][5][6] Therefore, stress related mechanisms might be manipulated by altering the spatial pressure distribution. To date, the primary focus of customizing the acoustic field has been to electronically steer the focus to track the kidney stone during treatment.…”
Section: Introductionmentioning
confidence: 99%